Influência do exercício físico sobre o estresse oxidativo, as MAPK e o NF-kB no músculo sóleo de ratos com insuficiência cardíaca induzida por estenose aórtica - Gomes, Mariana Janini [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: Heart failure is characterized by reduced physical capacity with early occurrence of fatigue and dyspnea. Skeletal muscle abnormalities have been considered responsible, at least partially, for the symptoms. Although increased oxidative stress participates in the pathophysiology of muscle abnormalities, sources of reactive oxygen species generation and their intracellular signaling pathways are not completely elucidated. Studies suggest that mitogen-activated protein kinases (MAPK) and the nuclear factor-kappaB (NF-kB) pathway are involved in muscle response to oxidative stress. Currently, guidelines recommend regular physical exercise for patients with stable heart failure. The effects of aerobic exercise on physical capacity and skeletal muscle changes during left ventricular persistent pressure overload have not been established. In this study, we evaluated the influence of aerobic exercise on oxidative stress, the MAPK and the NF-kB pathway in the soleus muscle of rats with aortic stenosis-induced heart failure. Methods: Twenty weeks after aortic stenosis induction, rats were assigned into four groups: sedentary control (C-Sed, n=22), exercised control (C-Ex, n=19), sedentary aortic stenosis (AS-Sed, n=18) and exercised aortic stenosis (AS-Ex, n=18). Exercise was performed on a treadmill, 5 times a week for 8 weeks. Physical capacity was assessed by maximal exercise test on a treadmill before and after the exercise period. Transthoracic echocardiography was performed before and after training. Activity of the antioxidant enzymes superoxide dismutase, glutathione peroxidase, and catalase, and lipid hydroperoxide concentration were evaluated by spectrophotometry. NADPH oxidase activity was analyzed by reduction of lucigenin and gene expression of its subunits NOX 2, NOX 4, p22phox, and p47phox by qPCR. Total generation of reactive oxygen species was measured by HPLC and protein expression by Western blot. Statistical ...

Introdução: A insuficiência cardíaca caracteriza-se por redução da capacidade física com ocorrência precoce de fadiga e dispneia. Alterações da musculatura esquelética têm sido responsabilizadas, pelo menos parcialmente, pelos sintomas. Embora aumento do estresse oxidativo participe da fisiopatologia das alterações musculares, as fontes de geração de espécies reativas de oxigênio e suas vias de sinalização intracelular ainda não foram completamente elucidadas. Estudos sugerem que as proteínas quinases ativadas por mitógeno (MAPK) e proteínas da via do fator nuclear-κB (NF-κB) estejam envolvidas na resposta muscular ao estresse oxidativo. Atualmente, as diretrizes recomendam a prática regular de exercícios físicos para pacientes com insuficiência cardíaca estável. Os efeitos do exercício aeróbio sobre a capacidade física e a musculatura esquelética durante sobrecarga pressórica persistente do ventrículo esquerdo não foram esclarecidos. Neste estudo avaliamos a influência do exercício aeróbio sobre o estresse oxidativo, as MAPK e o NF-κB no músculo sóleo de ratos com insuficiência cardíaca induzida por estenose aórtica. Métodos: Vinte semanas após indução de estenose aórtica, ratos Wistar foram alocados nos grupos controle sedentário (C-Sed, n=22), controle exercitado (C-Ex, n=19), estenose aórtica sedentário (EA-Sed, n=18) e estenose aórtica exercitado (EA-Ex, n=18). Exercício físico foi realizado em esteira, 5 vezes por semana, durante 8 semanas. A capacidade física foi avaliada por teste de esforço máximo em esteira antes e após o período de exercício. Ecocardiograma transtorácico foi realizado antes e após o treinamento. A atividade das enzimas antioxidantes superóxido dismutase, glutationa peroxidase e catalase e a concentração do hidroperóxido de lipídeo foram avaliados por espectrofotometria. A atividade da NADPH oxidase foi analisada pela redução de lucigenina e a...
Keywords: Insuficiencia cardiaca; Stress oxidativo; Sistema musculoesquelético; Exercícios físicos; Oxidative stress